2016
DOI: 10.1139/cjps-2015-0213
|View full text |Cite
|
Sign up to set email alerts
|

Expression study of soybean germin-like gene family reveals a role ofGLP7gene in various abiotic stress tolerances

Abstract: Germin-like proteins (GLPs) are ubiquitous plant glycoproteins (belonging to the cupin super family) that play diverse roles, including abiotic stress resistance in many plant species. To identify the molecular functions underlying abiotic stress responses, the expression of germin-like protein encoding genes of soybean GmGLPs was analyzed. qRT-PCR analyses of 21 GmGLPs transcripts abundances were conducted in soybean leave tissues. The results showed that GmGLPs transcripts were highly abundant upon treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…One of the main roles of the proteins mentioned above is triggering the abiotic stress-tolerance in many plant species. Li et al (2016) revealed that GLP transcripts were plentiful after treatment with high salinity, PEG6000, abscisic acid, and methyl viologen in soybean. Arabidopsis plants overexpressing a GLP from soybean indicated enhanced drought, salt, and oxidative tolerance [58].…”
Section: Functional Analysis Of Salt-regulated Genes Using Mapmanmentioning
confidence: 99%
“…One of the main roles of the proteins mentioned above is triggering the abiotic stress-tolerance in many plant species. Li et al (2016) revealed that GLP transcripts were plentiful after treatment with high salinity, PEG6000, abscisic acid, and methyl viologen in soybean. Arabidopsis plants overexpressing a GLP from soybean indicated enhanced drought, salt, and oxidative tolerance [58].…”
Section: Functional Analysis Of Salt-regulated Genes Using Mapmanmentioning
confidence: 99%
“…Previous studies have suggested that extracellular germins and germin-like proteins (GLPs) could be induced by a range of abiotic or biotic stresses, such as herbivores 7 , 8 , drought 9 , 10 , salinity 8 , 11 and they are considered to be the pathogenesis-related proteins (PRs) 16 family due to their disease resistance property 12 14 . Germins and GLPs were first characterized in wheat ( Triticum aestivum ) and constitute a large plant gene family 15 .…”
Section: Introductionmentioning
confidence: 99%
“…All peanut GLPs changed their expression levels (were mostly transiently induced) in response to exogenous applications of ABA in seedlings (Wang et al 2013 ). In soybean, GLPs from leaves accumulated in response to ABA and PEG (Li et al 2016 ). The expression of the rice germin-like protein OsGLP2-1 is increased in response to ABA and has been shown to be involved in the regulation of seed dormancy (Wang et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%